Актуальні проблеми досудового розслідування кримінальних правопорушень у сфері професійної діяльності журналістів - Юхно, О. О.; Yukhno, O. O.; Олександр Юхно (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 11–20, 2017)
Проаналізовано чинне кримінальне і кримінальне процесуальне законодавство, що регулює захист прав, свобод і законних інтересів журналістів при здійсненні ними професійної діяльності під час досудового розслідування, та інші закони з цих питань. Виявлено певні неузгодженості, недоліки, прогалини і неврегульованість окремих питань журналістської діяльності в чинному законодавстві, що негативно впливають на своєчасну реєстрацію, кваліфікацію та на стан досудового розслідування злочинів у сфері професійної діяльності журналістів. Надано пропозиції щодо вдосконалення законодавства з цих питань та взаємодії журналістів з органами досудового розслідування.

The author has analyzed the current criminal and criminal procedural legislation of Ukraine regulating the protection of the rights, freedoms and legal interests of journalists in exercising their professional activities, which is used during the pre-trial investigation to assess the committed crimes in this area, as well as other laws on the above mentioned and other issues. Some inconsistencies, disadvantages, gaps and unsettled issues, in particular the journalistic activity itself, and directly the pre-trial investigation, which take place in the current legislation, have been revealed. The said negatively affects the timely registration, qualification and the state of pre-trial investigation of crimes committed in order to counteract the professional activities of journalists and in general, the authority of both law enforcement and other state agencies. Propositions for improving the regulatory base on these issues have been provided. The author has also provided propositions to improve the interaction of journalists with pre-trial investigation agencies in order to use the acquired information and evidence by journalists for successful and effective use in the investigation of criminal proceedings of such a category, as well as in order to protect their rights, freedoms and legitimate interests, up to court hearings. The court practice concerning the consideration of criminal proceedings (cases) on the studied category of crimes has been analyzed and the relevant propositions according to the established research results have been provided. Besides, the author has presented suggestions regarding the recognition of victims journalists themselves, along with close relatives of journalists, in certain categories of criminal offenses. The peculiarities of collection, recording, evaluation of evidence and carrying out certain investigative actions in the area of antiterrorist operation have been established. Besides, the author has provided recommendations for training journalists for law enforcement agencies at higher educational institutions of the Ministry of Internal Affairs of Ukraine and the Ministry of Justice of Ukraine, as well as conducting introductory optional courses on legal profession for working journalists.

Проанализировано действующее уголовное и уголовное процессуальное законодательство, регулирующее защиту прав, свобод и законных интересов журналистов при осуществлении ими профессиональной деятельности во время досудебного расследования, и другие законы по этим вопросам. Выявлены определённые несоответствия, недостатки, пробелы и неурегулированность отдельных вопросов журналистской деятельности в действующем законодательстве, которые негативно сказываются на своевременной регистрации, квалификации и на состоянии расследования преступлений в сфере профессиональной деятельности журналистов. Даны предложения по совершенствованию законодательства по этим вопросам и взаимодействию журналистов с органами досудебного расследования.
Relevant problems of pre-trial investigation of criminal offenses in the field of professional activity of journalists
Актуальные проблемы досудебного расследования уголовных правонарушений в сфере профессиональной деятельности журналистов
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; розслідування кримінальних правопорушень; журналісти; професійна діяльність; перешкоджання професійної діяльності журналістів; обмін інформацією; взаємодія; родичі і члени сім’ї; investigation of criminal offenses; journalist; professional activity; opposing the activity; obstruction; exchange of information; interaction; relatives and family members; журналисты; профессиональная деятельность; препятствование профессиональной деятельности журналистов; противодействие деятельности; обмен информацией; взаимодействие; родственники и члены семьи